2015
DOI: 10.1080/13549839.2015.1038986
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, agency and collective action as barriers to energy-saving behaviour

Abstract: Energy saving is becoming a rising priority as a response to climate change and fossil-fuel depletion in recent years. However, despite energy-related behaviour change being an important part of many environmental education initiatives, 'energy literacy' among citizens remains patchy in both the US and the UK, with evidence of strong positive attitudes but less consistent knowledge. Whilst it is clear that increasing knowledge does not automatically produce behaviour changes, potential questions must be asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 42 publications
5
27
1
Order By: Relevance
“…The findings by Pothitou, et al, [25] and Cotton, et al, [26] are confirmed by some of the results of this study. For instance, the survey participants were asked if they opened a window to allow fresh air in the house while their air-conditioning systems are on, see Figure 2.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The findings by Pothitou, et al, [25] and Cotton, et al, [26] are confirmed by some of the results of this study. For instance, the survey participants were asked if they opened a window to allow fresh air in the house while their air-conditioning systems are on, see Figure 2.…”
Section: Resultssupporting
confidence: 89%
“…Research in Ireland and Brazil has also indicated that an improvement in insulation and enhanced energy efficiency measures in buildings can contribute significantly in reducing energy consumption [24,25]. The link between environmental knowledge and energy conservation was found to exist in a study conducted by Cotton et al [26]. The study found that, in general terms, simply directing and encouraging energy conservation behaviour is not sufficient to change consumption habits.…”
Section: Qatar: Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In this set of statements, BU is highest on "Turning off lights when they are not in use" as well as "Turn down the heat", and UBI (PT) is superior in "Avoid charging mobile phones overnight". The latter behaviour is one that is infrequently reported across all universities and is an issue which is generally poorly understood by students (Cotton et al, 2015b). By observing the results of F statistics, all the variables are significant for differentiating between the groups (p< 0,05) except the variable "Try to save water" (p>0,05), which nonetheless allows us to reject H 2 .…”
Section: Resultsmentioning
confidence: 79%
“…Some questions were also posed to gather demographic information such as age, gender and nationality. (See Cotton et al, (2015b) for further information about survey development.) After collection, the data were analysed and interpreted using the statistical software SPSS 21.0 (Statistical Package for Social Sciences).…”
Section: Methodsmentioning
confidence: 99%